2008
DOI: 10.3390/ijms9112146
|View full text |Cite
|
Sign up to set email alerts
|

T-2 Toxin-induced Toxicity in Pregnant Mice and Rats

Abstract: T-2 toxin is a cytotoxic secondary fungal metabolite that belongs to the trichothecene mycotoxin family. This mycotoxin is a well known inhibitor of protein synthesis through its high binding affinity to peptidyl transferase, which is an integral part of the ribosomal 60s subunit, and it also inhibits the synthesis of DNA and RNA, probably secondary to the inhibition of protein synthesis. In addition, T-2 toxin is said to induce apoptosis in many types of cells bearing high proliferating activity. T-2 toxin re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 66 publications
(70 reference statements)
0
46
0
1
Order By: Relevance
“…In animal experiments, placental apoptosis is induced by such things as glucocorticoid (3), lipopolysaccharide [49], T-2 toxin [50], busulfan [51], and some anticancer drugs [52,53]. In a previous study [46], TUNEL-positive cells found in fetal and maternal part of the placenta were counted on gestation day 20 and the number of apoptotic cells in the maternal part was reported to be higher than the ones in the fetal part.…”
Section: Discussionmentioning
confidence: 97%
“…In animal experiments, placental apoptosis is induced by such things as glucocorticoid (3), lipopolysaccharide [49], T-2 toxin [50], busulfan [51], and some anticancer drugs [52,53]. In a previous study [46], TUNEL-positive cells found in fetal and maternal part of the placenta were counted on gestation day 20 and the number of apoptotic cells in the maternal part was reported to be higher than the ones in the fetal part.…”
Section: Discussionmentioning
confidence: 97%
“…However, on the basis of previous reports (Bensassi et al, 2012;Ma et al, 2012), it is plausible that DON also exerts its toxicity through oxidative stress. Considering the overall mechanism of cytotoxic effects of DON and T-2 toxin, it is presumed that oxidative stress in addition to protein synthesis inhibition (Dänicke, 2006;Doi et al, 2008;Pestka, 2008) in cells is importantly involved.…”
Section: Figmentioning
confidence: 99%
“…Its acute toxicity is higher than in other mycotoxins (Visconti, 1991). During the acute exposure to high doses of T-2 toxin, in animals exhibit "radiomimetic" symptoms, while extremely high doses can cause cardiovascular dysfunction resemble a shock-like syndrome that can result in death (Ueno, 1984;Doi et al, 2008). T-2 toxin induce some alterations in the membrane structure, which consequently stimulates lipid peroxidation.…”
mentioning
confidence: 99%